Damping property of prepacked concrete incorporating coarse aggregates coated with polyurethane. (October 2018) - Lee, Kang Seok; Choi, Jeong-Il; Park, Se Eon; Hwang, Jae-Seung; Lee, Bang Yeon
Abstract: This study proposes a new prepacked concrete incorporating coarse aggregates coated with polyurethane with high damping and investigates the mechanical properties and damping ratio of the proposed concrete. Two types of prepacked concretes, in this case new prepacked concrete produced with the materials and manufacturing process as proposed here and normal prepacked concrete were prepared. A series of experiments focusing on the density, strength, and impact test results of small-scale specimens and beam specimens as well as a modal analysis of a simply-supported beam were conducted in an effort to characterize the mechanical and damping properties of the new prepacked concrete. The test results showed that the damping ratio of the new prepacked concrete was as high as 10% in the range of 10 Hz to 200 Hz, which is approximately 10 times higher than that of normal prepacked concrete, with a decrease in the mechanical properties.